A Comparative Analysis of Banking’s Financial Performance before and after using E-Money - Preatmi Nurastuti; Adrianna Syariefur Rahman (DPPM Universitas Pelita Bangsa, 2023)
This study aims to determine the comparison of the financial performance of PT. Bank Mandiri (Persero) Tbk before and after issuing e-money. By using a research period of 3 years before and 3 years after issuing e-money. Financial performance is measured by profitability ratios as seen from the Return On Assets (ROA), Return On Equity (ROE), and BOPO ratios. This research is a quantitative research. The data used in this study is secondary data, namely the financial statements of PT. Bank Mandiri (Persero) Tbk. The subject of this research is PT. Bank Mandiri (Persero) Tbk which issues e-money. Data analysis used paired sample t-test analysis. The results of this study indicate that there are significant differences in the ratios of ROA, ROE, and BOPO before and after issuing e-money